importance of conservancies for enhancing the value of game ranch land for large mammal conservation in southern Africa - Lindsey, P.A; Romañach, S.S; Davies-Mostert, H.T (Journal of zoology (1987), 2009)
Legislative changes during recent decades resulted in a massive shift away from livestock towards game ranching in southern Africa, resulting in significant increases in the abundance and distribution of many wildlife species. However, there are problems associated with game ranching from a conservation perspective, including persecution of predators, overstocking, introductions of exotic species and genetic manipulation of 'huntable' species. We suggest here that most of these problems could be overcome through promoting the formation of conservancies, where adjacent ranches remove internal fencing to form larger collaborative wildlife areas. Larger areas permit the reintroduction of the full range of indigenous mammals, tending to result in a land-use shift from high-offtake, low-value consumptive utilization towards higher value forms of hunting and ecotourism. Under these land-use conditions, ranchers tend to be more tolerant of predators and often actively reintroduce them. Freedom of movement for wildlife populations increases resilience to environmental shocks. The collaborative management agreements typical of conservancies tend to align more closely with conservation objectives than on single ranches. Fortuitously, there are financial advantages associated with conservancies: land-use options in conservancies are more profitable and there are economies of scale associated with cooperative management. Land within conservancies is likely to appreciate in value and attract external investment. In addition, conservancies are more conducive to developing partnerships with indigenous communities and investors and may thus increase the political and social sustainability of game ranching. However, ranchers are fiercely independent and may be resistant to removing fences due to the perception that they may relinquish control over their land and wildlife. Strategies are required to overcome such reluctance and promote the formation of conservancies to enhance the conservation value of game ranch land.